Monitoring Kamera Pengintai Jarak Jauh Terintegrasi dengan Google Drive Berbasis Raspberry Pi Via Internet - Angga Yolanda Putra . (Faculty of Engineering, Universitas Tanjungpura, 2015)
CCTV is surveillance camera system that allows the users to monitoring remotely. This will help in monitoring places that has high level of mobilization, but uneffectively for places that has low level of mobilization suchs storage room and residences. In this paper designed surveillance camera based on Raspberry Pi specialized for low level of mobilization that can be monitorized remotely. Raspberry Pi surveillance camera system will only record when it detected any movements on the camera, then automatically save the recorded video to Google Drive and sent the notification to the user. Based on WiFi USB test, result showed that Raspberry Pi connected with Router of Telecommunication Laboratory of Engineering Faculty of Tanjungpura University and get IP Address which 192.168.0.105. Based on LCD 16x2 test when the program is running, gets that LCD showed date of “24th, may” time “08:38:11” and IP Address that connected with Raspberry Pi 192.168.0.105. Based on surveillance testing running with Tablet Advan T1J+ that connected with GSM network, the result is the program running smoothly. Based on surveillance camera monitoring test of Raspberry Pi, gets the average value of response time for testing using Laptop device with 5 meter distance from Access Point is 8,6 second and distance of 25 meter from Access Point is 8,2 second, meanwhile the average value of response time for testing using Tablet Advan T1J+ device is 8,2 second. Time between on page response monitoring happened based on 2 factors which from RAM Raspberry Pi for testing still running at 512 MB and internet connection. Replacement model of Raspberry Pi that have larger RAM fitur from then can be done so video streaming that showing live in real-time. Average speed of page response monitoring time on every test relatively the same, this is based on how big the available bandwidth is and the bandwidth to run the internet network. The result of integration test between Raspberry Pi and Google Drive, gets that recorded tape result saved nicely on Google Drive and give notification to the user. The notification sent to the Table Advan T1J+ with message of “” BULGAR !!!” video recording successfully saved on Google Drive”. Based on GPIO test, shows that Email receive new message from video record result, so blue indicator LED on. Key words: Raspberry Pi, CCTV, WiFi USB, LCD 16x2, Google Drive, Email, GPIO.